A potent antifungal agent for basal stem rot disease treatment in oil palms based on chitosan-dazomet nanoparticles - Maluin, Farhatun Najat; Hussein, Mohd Zobir; Yusof, Nor Azah; Fakurazi, Sharida; Abu Seman, Idris; Zainol Hilmi, Nur Hailini; Jeffery Daim, Leona Daniela (MDPI, 2019)
The use of nanotechnology could play a significant role in the agriculture sector, especially in the preparation of new-generation agronanochemicals. Currently, the economically important plant of Malaysia, the oil palm, faces the threat of a devastating disease which is particularly caused by a pathogenic fungus, Ganoderma boninense. For the development of an effective antifungal agent, a series of chitosan nanoparticles loaded with a fumigant, dazomet, were prepared using various concentrations of sodium tripolyphosphate (TPP)—2.5, 5, 10, and 20 mg/mL, abbreviated as CDEN2.5, CDEN5, CDEN10, and CDEN20, respectively. The effect of TPP as a crosslinking agent on the resulting particle size of the synthesized nanoparticles was investigated using a particle size analyzer and high-resolution transmission electron microscopy (HRTEM). Both methods confirmed that increasing the TPP concentration resulted in smaller particles. In addition, in vitro fumigant release at pH 5.5 showed that the release of the fumigant from the nanoparticles was of a sustained manner, with a prolonged release time up to 24 h. Furthermore, the relationship between the chitosan-dazomet nanoparticles and the in vitro antifungal activity against G. boninense was also explored, where the nanoparticles of the smallest size, CDEN20, gave the highest antifungal efficacy with the lowest half maximum effective concentration (EC50) value of 13.7 ± 1.76 ppb. This indicates that the smaller-sized agronanoparticles were more effective as an antifungal agent. The size can be altered, which plays a crucial role in combatting the Ganoderma disease. The agronanoparticles have controlled release properties and high antifungal efficacy on G. boninense, thus making them a promising candidate to be applied in the field for Ganoderma treatment.